THE EFFECT OF SOCIAL COMMERCE CONSTRUCT AND BRAND IMAGE ON CONSUMER TRUST AND PURCHASE INTENTION - Zamrudi, Zakky; Suyadi, Imam; Abdillah, Yusri (Profit: Jurnal Adminsitrasi Bisnis, 2016)
Social commerce is a new development of e-commerce by using social media platform to interact on the internet. Current studies only examine the model on its own basis by using direct effect only. This research examines both of the model together to reveal which factor that give the greater effects against consumer trust and purchasing intention both direct effect, indirect effects and total effects. Drawing a literature from marketing and information systems (IS) the author proposes a model to understand the relationship between social commerce construct and the brand image against the purchasing intention in Instagram. The study utilized Generalized Structured Component Analysis (GSCA) methodology to test the model. The research object was the @fujifilm_id instagram followers as many as 99 respondents. Results shows that social commerce construct are likely to give greater effect against the purchase intention rather than by the brand image whether in direct, indirect and total effect. Yet, the brand image is a crucial part of a brand which is needed to be maintained against customer perspective. Implication, limitation, discussion and future research direction are also discussed.Â Â